Capital Account Openness in Low-income Developing Countries : Evidence from a New Database - Jahan, Sarwat (IMF Working Papers; Working Paper, 2016)
The relevance of recording and assessing countries' capital flow management measures is well-recognized, but very few studies have focused on low-income developing countries (LIDCs). A key constraint is the lack of an appropriate index to measure the openness of capital account and its change over time. This paper fills the gap by constructing a de jure index based on information contained in the IMF's Annual Report on Exchange Arrangements and Exchange Restrictions. It provides an aggregate index to capture the overall openness of the capital account, and also provides a breakdown of openness for various subcategories of capital flows. The new database covers 164 countries with information on 12 types of asset categories over the period 1996-2013. The index provides the largest coverage of LIDCs among all existing indices and also provides granularity on openness across asset types, direction of flows and residency. The paper examines the link between de jure capital account openness with de facto capital flows and outlines potential applications of this database.